A new platform for global health research and policy exchange and communication. Issue 1 (December 2016) - Chen, Xinguang
Abstract Peer-reviewed publications are essential to promote the development of global health sciences. Wuhan University Global Health Institute, in partnership with BioMed Central, launchesGlobal Health Research and Policy (GHRP ) as an open access journal to meet the needs of all authors and readers who are interested in global health. Our publication priorities include both empirical and implementation research, research methodologies, and global health education, as well as opinions and discussion over the concept of global health sciences and its development in the future.